Parallel corpus-based bilingual terminology extraction - Gómez Guinovart, Xavier (2009)
This paper presents a parallel corpora-based bilingual terminology extraction method based on the occurrence of bilingual morphosyntactic patterns in probabilistic translation dictionaries. We discuss an experiment focused on two language pairs – English-Galician and English-Portuguese, and show results which experimentally confirm the high degree of accuracy of the proposed extraction technique.